The Vowel [ы] in the Speech of Russians in Lithuania - Балшайтите, Дануте (Slavistica Vilnensis, 2009)
Diphthongalization – an increase in the frequency of the second formant at the beginning of the vowel phonation from the lower position to the higher one at the acoustic level – differentiates the vowel [ы] from the rest of Russian vowels.The article discusses the acoustic parameters (the initial frequency of the second formant, the frequency of the second formant at the stationary site, and size and duration of the overfall of the second formant) of the transitional site of the stressed vowel [ы] in the speech of Russians living in Lithuania. According to the obtained data, Russian speakers keep the diphthongalization of [ы] in the same manner as in the codified Russian pronunciation. The heterogeneity of the pronunciation of [ы] in the speech of Russians in Lithuania is most clearly manifested in the syllables with labial consonants, namely in a position after the labial consonants the initial phase of [ы] is characterized by the biggest overfall of the second formant (with the exception of the [ы] positioned after [f]) and by the longest duration (except for the position of [ы] following [p]). The pronunciation of [ы] by Russians in Lithuania is also distinguished by a different speed of change in the second formant. The rapid increase in the second formant frequency of [ы] is most typical of the syllables with front dental consonants (with the exception of syllables with [l]), while a smooth increase in the second formant of [ы] is typical of syllables with labial consonants, except for the syllables with [p].